Novel insight into elemental mercury removal by cobalt sulfide anchored porous carbon: Phase-dependent interfacial activity and mechanisms. (1st January 2023) - Shen, Fenghua; He, Shudan; Li, Junyuan; Wang, Pingshan; Liu, Hui; Xiang, Kaisong
Highlights: Phase-dependent interfacial activity of cobalt sulfide to Hg 0 has been elucidated. CoS2 phase is more active in Hg 0 oxidation than Co9 S8 phase. Co site on CoS2 (1 1 1) surface represent the most active site to react with Hg 0 . CoS2 anchored carbon contribute to an excellent material for gaseous Hg 0 capture. Abstract: Construction high-activity phase of metal sulfides on low-cost carbon represents a judicious way to develop advanced environmental materials, and yet the interrelation between crystal phase of metal sulfides on carbon matrix and interfacial reactivity of the composites towards gaseous elemental mercury (Hg 0 ) has not been explored. Herein, we clarified the mechanisms of crystal phase in determining the Hg 0 oxidation and adsorption activity of cobalt sulfide anchored carbon for the first time. Both CoS2 and Co9 S8 phases were employed as model and synthesized on the same porous carbon matrix. The sulfur-rich phase of CoS2 anchored carbon has obvious advantages in providing Co 3+ and S2 2- species comparison to Co9 S8 anchored carbon, which act as reaction centers for Hg 0 . The CoS2 anchored carbon shows a high Hg 0 adsorption capacity of 16.2 mg·g −1, which is superior to various activated carbons and metal sulfides. Surprisingly, the composite is able to utilize O2 and SO2 in flue gas to regenerate the consumed Co 3+ sites, which is ascribed to the use of carbon as matrix. Both experimental and theoretical results confirm that Co sites represent the most active center for Hg 0 adsorption. This work provides a new paradigm in design and engineering of high-performance materials in environmental remediation.